Hemicolectomy Does Not Provide Survival Benefit for Right-Sided Mucinous Colon Adenocarcinoma - Huang, Jia; Huang, Qiulin; Tang, Rong; Chen, Guodong; Zhang, Yiwei; He, Rongfang; Zu, Xuyu; Fu, Kai; Peng, Xiuda; Xiao, Shuai (Frontiers in Oncology, 2021)
Background The extent of bowel resection is widely debated in colon cancer surgery. Right hemicolectomy (RHC) and partial colectomy (PC) are the most common operation options for right-sided colon cancer (RCC). However, there are still no treatment guidelines or published studies to guide surgical options for mucinous adenocarcinoma (MAC) of RCC. Methods Patients with MAC and non-specific adenocarcinoma (AC) of RCC who underwent RHC and PC from 2010 to 2015 in the Surveillance, Epidemiology, and End Results (SEER) database were retrieved. The general characteristics and survival were compared and analysed. Results A total of 27910 RCC patients were enrolled in this study, among them 3413 were MAC. The results showed that race, carcinoembryonic antigen (CEA) level, perineural invasion (PNI), tumour size, tumour location, TNM stage, liver metastasis, chemotherapy were significantly different between MAC and AC groups. The MAC group had the similar dissected lymph nodes, but more positive lymph nodes than AC group. The overall survival (OS) of MAC group was poorer than AC group, but the cancer-specific survival (CSS) was similar between the two groups. The RHC subgroup of the MAC group had more patients of age ≤ 60 years, larger tumour size, cecum/ascending colon location and dissected lymph nodes than the PC subgroup, but similar positive lymph nodes, perioperative mortality, OS and CSS as the PC subgroup. Moreover, the univariate and multivariable analysis for the survival of RCC patients with MAC showed that RHC might not be a superior predictor for OS and CSS compared with PC. Conclusions RHC could not dissect more positive lymph nodes or provide long-term survival benefits for RCC patients with MAC compared with PC. This study could provide some evidence for surgery treatment selection for MAC of RCC, which has important clinical value in individual management for colon cancer patients.